Prevalence of sacral spina bifida occulta with lumbosacral transitional vertebra in a skeletal collection of a South African population - Shahed Nalla; Juan A. Sanchis-Gimeno; Glen J. Paton (Elsevier, 2024)
In this study, complete Sacral Spina Bifida Occulta (SSBO) and Lumbosacral Transitional Vertebrae (LSTV) with their various subtypes based on the Castellvi classification were appraised in a South African population sample. Adult human skeletons representing the three largest South African population groups, namely South African African, South African of Mixed Ancestry; South African of European descent; both biological sexes; and age range between 21 and 90 years at death were evaluated for both spinal anomalies.The number of preselected skeletons (n = 1798) from the largest collection in Africa of modern human skeletons (N = 2630) provided a strong representative South African sample. The observational study looked at lumbar and sacral vertebrae in each skeleton and any anomalous features were captured in an Excel spreadsheet.Complete SSBO with no LSTV was observed in eight subjects (8/1798; 0.44 %), while incomplete SSBO was observed in one subject (1/1798; 0.06 %), and one individual (1/1798; 0.06 %) exhibiting complete SSBO with LSTV (Type IIIB, Castellvi classification). No significant differences were observed when comparing the prevalence of the LSTV with SSBO in the male and female groups of the different population affinity groups. The number of individuals with SSBO was found in more South African Africans than in the other population groups with no significant difference between groups.This research revealed the simultaneous presence of two morphological anomalies (SSBO and LSTV) at the same vertebral segment that could result in low back pain. Variant morphology awareness is crucial for clinicians across all modalities to prevent misdiagnosis, leading to better treatment plans, and avoiding injury.